Joel Martins: Ensaio biográfico sobre um educador - Lima, José Antonio (2005)
The objective of this research is to collect and analyse data related to the biography of Joel Martins, demonstrating his trajectory and his importance for Education. Joel Martins contribution in the context of Brazilian Education, more specifically in the area of Educational Psychology, was remarkable for his new perspectives and approaches not only in theoretical questions but also in practice, for he broke through paradigms, incentivated and promoted researches with the spirit of an achiever and above all for his outstanding personality, which has been influencing his peers. At the same time it is necessary to enhance his relevant role at PUCUSP in several different aspects. The biographical method was used here, making it possible to compose Joel Martins biography. Documental and biographical sources were used, as well as interviews with people who knew him. In the conclusion the collection of data and the crossing of different information (personal, professional and some curiosities) were used, so that an outline of the character could be built under three aspects: his way of being, his intelectual characteristics and his commitment with knowledge and finally, his professional life and his commitment towards Education and University